STRATEGI PENGEMBANGAN FINTECH PADA PRODUK DAN LAYANAN di BANK SYARIAH - Yulisa Khairani; Hesi Eka Puteri (CV. Adiba Aisha Amira, 2024)
Financial technology is an innovation in the field of financial services that performs financial transactions with the Internet system. Fintech encourages the banking sector to adapt and adapt in an increasingly advanced and evolving technological age. This study aims to analyze fintech applications in sharia banking and design appropriate development strategies regarding fintech at Bank BSI KC Bukittinggi. This type of research is research with descriptive qualitative approach in which data analysis uses SWOT matrix to determine opportunities and challenges Data collection was carried out by interview and documentation method with Branch Office Service Manager and Costumer Service Bank BSI KC Bukittinggi. The results of this study are that there are many advantages obtained by using fintech and a suitable fintech development strategy, namely the SO (Stregth - Opportunities) strategy. The strategy of harnessing power to gain opportunities is: 1. Creating and facilitating business operators (MSMEs), students and the general public with the choice of technology access to products and services, 2. Always pay attention to the market share and innovate on the existing financial technology of the Bank, 3. Improving and guaranteeing the quality of service for customers, 4. Expanding the network of Fintech services so that it is expected that Bukittinggi city will have even access to financial technology.